Beyond Parental Income: The Crucial Role Of Lifestyle And Literacy In Gen Z Financial Habits - Ni Made Sri Ayuni; Ni Wayan Novi Budiasni (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to examine the influence of financial literacy and parental income on financial management behavior, with lifestyle as a mediating variable among Generation Z in Temukus Village. A quantitative approach was employed, using questionnaires distributed via Google Forms as the data collection method, with a Likert scale as the measurement tool. The respondents consisted of 94 individuals from Generation Z, aged between 17 and 28 years. The data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach through the SmartPLS application. The findings reveal that financial literacy has a positive and significant effect on both financial management behavior and individuals’ lifestyles. On the other hand, parental income significantly influences lifestyle but does not have a direct significant effect on financial management behavior. Lifestyle also has a positive and significant effect on financial management behavior and serves as a partial mediator in the relationship between financial literacy and parental income with financial management behavior.